IMAGE QUALITY ANALYSIS OF AN INDUSTRIAL INSTANT NON-SCANNING TOMOGRAPHY SYSTEM WITH DIFFERENT COLLIMATORS - Alexandre França Velo; Alexandre Gimenes Alvarez; Margarida Mizue Hamada; Carlos Henrique de Mesquita (Brazilian Journal of Radiation Sciences)
The greatest impact of the computed tomography (CT) applications currently occurs in medicine. In industry there is much interest of using CT in order to know the interior of: (i) industrial objects; (ii) machines and their means of production. The purpose of this tomography is to: (a) control the quality of the final product and (b) optimize production and analyze the quality of the means of production. An instant non-scanning tomography system is being developed at the IPEN. This tomography comprised different collimators was simulated with Monte Carlo using the MCNP4C. The image quality was evaluated with Matlab® 2013b analyzing the contrast to noise (CNR), root mean square ratio (RMSE), signal to noise ratio (SNR) and the spatial resolution by the Modulation Transfer Function (MTF(f)), to identify which collimator fits better to the tomography in development. It was simulated three situations; (i) with no collimator; (ii) ø 25x 50 mm2 cylindrical collimator with a septum of ø5.0 x 50 mm2; (iii) ø25 x 50 mm2 cylindrical collimator with a slit septum of 24 x 5.0 x 50 mm3. RMSE values for no collimator presented better results. CNR showed that no collimator and slit collimator reaches the same CNR values, but no collimator decreases more than the slit collimator as the number of iteration rises. The hole collimator reaches a higher CNR value, however decreases more than the others. The spatial resolution with no collimator and slit collimator were around 31.9 mm, and for the hole collimator was around 20 mm